Proteobacteria and Bacteroidetes are major phyla of filterable bacteria passing through 0.22 μm pore size membrane filter, in Lake Sanaru, Hamamatsu, Japan. Issue 7 (3rd July 2018) - Maejima, Yoshiaki; Kushimoto, Koya; Muraguchi, Yusuke; Fukuda, Kohei; Miura, Takamasa; Yamazoe, Atsushi; Kimbara, Kazuhide; Shintani, Masaki
Abstract: 141 filterable bacteria that passed through a 0.22 μm pore size filter were isolated from Lake Sanaru in Hamamatsu, Japan. These belonged to Proteobacteria, Bacteroidetes, Firmicutes, or Actinobacteria among which the first two phyla comprised the majority of the isolates. 48 isolates (12 taxa) are candidates assignable to new bacterial species or genera of Proteobacteria or Bacteroidetes .